Long-chain GM1 gangliosides alter transmembrane domain registration through interdigitation - Manna, Moutusi; Javanainen, Matti; Monne, Hector Martinez-Seara; Gabius, Hans-Joachim; Rog, Tomasz; Vattulainen, Ilpo (Biochimica et biophysica acta. Biomembranes, 2017)
Extracellular and cytosolic leaflets in cellular membranes are distinctly different in lipid composition, yet they contribute together to signaling across the membranes. Here we consider a mechanism based on long-chain gangliosides for coupling the extracellular and cytosolic membrane leaflets together. Based on atomistic molecular dynamics simulations, we find that long-chain GM1 in the extracellular leaflet exhibits a strong tendency to protrude into the opposing bilayer leaflet. This interdigitation modulates the order in the cytosolic monolayer and thereby strengthens the interaction and coupling across a membrane. Coarse-grained simulations probing longer time scales in large membrane systems indicate that GM1 in the extracellular leaflet modulates the phase behavior in the cytosolic monolayer. While short-chain GM1 maintains phase-symmetric bilayers with a strong membrane registration effect, the situation is altered with long-chain GM1. Here, the significant interdigitation induced by long-chain GM1 modulates the behavior in the cytosolic GM1-free leaflet, weakening and slowing down the membrane registration process. The observed physical interaction mechanism provides a possible means to mediate or foster transmembrane communication associated with signal transduction.
Keywords: Glycosphingolipid; Lipid Bilayers; simulace molekulární dynamiky; lipidové dvojvrstvy; G(M1) gangliosid; membrane domain; G(M1) Ganglioside; membrane registry; Molecular Dynamics Simulation; cholesterol; computer simulations; molecular dynamics